2015
DOI: 10.1387/revpsicodidact.13854
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Relevant Elements for Promoting Effective Interventions in Old Age // Identificación de elementos relevantes para promover intervenciones eficaces en la vejez

Abstract: The aim of this review is to identify relevant elements that ensure the effectiveness and efficiency of empirically based interventions (EBI), contrasting virtual and face-to-face intervention on active aging variables based on these indicators. We selected and encoded the 38 intervention studies (24 face-to-face, 12 virtual and 2 both modalities). These studies focus on six dimensions of quality of life, were published in the last decade and provide us data that allow the calculation of effect size and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
(8 reference statements)
0
2
0
1
Order By: Relevance
“…Although most studies in the current meta-analysis were cross-sectional studies, 4 out of the 59 studies were based on intervention. It is necessary to report treatment fidelity of these intervention studies to ensure that study outcomes were due to treatment rather than factors incidental to the intervention (Díaz-Prieto and García-Sánchez, 2015; Canedo-García et al, 2017). Table 1 showed the treatment fidelity of the four intervention studies in the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Although most studies in the current meta-analysis were cross-sectional studies, 4 out of the 59 studies were based on intervention. It is necessary to report treatment fidelity of these intervention studies to ensure that study outcomes were due to treatment rather than factors incidental to the intervention (Díaz-Prieto and García-Sánchez, 2015; Canedo-García et al, 2017). Table 1 showed the treatment fidelity of the four intervention studies in the meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the heterogeneity of different outcome indicators (e.g., family ties increased, feeling of social support, social relationship), meta-analysis is not suitable for use. According to the analysis method of the three previous evaluations (Díaz and García, 2016;Canedo-García et al, 2017;Li et al, 2018), narrative synthesis and vote-counting methods were used to summarize and interpret study data. The current review was reported in accordance with the latest PRISMA guidance (Page et al, 2021).…”
Section: Review Strategymentioning
confidence: 99%
“…La participación en este tipo de actividades, además de restar valor a los estereotipos sobre la vejez (Gázquez et al, 2009), tiene una repercusión positiva en la integración social, en la salud física y mental de los alumnos (Gázquez, Pérez-Fuentes, & Carrión, 2010), así como en el mantenimiento de las funciones cognitivas (Plaza, Requena, Rosario, & López, 2015). De los beneficios derivados de las diferentes iniciativas para la mejora de la calidad de vida en personas mayores, se extrae la necesidad de identificar nuevos elementos para el diseño y la promoción de intervenciones eficaces (Díaz-Prieto & García-Sánchez, 2015).…”
Section: Introductionunclassified